The p53 family: function and molecular mechanisms - Melino, Gerry (Henry Stewart Talks, 2007)
The p53/p63/p73 family, DNA damage elicits repair mechanisms involving the tumour suppressor gene p53 and the two newer members of the same family: p63 and p73, The molecular events driven by DNA damage to elicit the function of p63/p73 and their transcriptional regulation, The biological effect of p63/p73 in the immune and neural systems